Real‐world study of lazertinib as second‐line or greater treatment in advanced non‐small cell lung cancer - Jeong Uk Lim; Kyuhwan Kim; Kyu Yean Kim; Hye Seon Kang; Ah. Young Shin; Chang Dong Yeo; Sung Kyoung Kim; Chan Kwon Park; Sang Haak Lee; Seung Joon Kim (Thoracic Cancer, 2024)
Abstract Background Lazertinib is an oral, third‐generation EGFR‐TKI, which specifically targets the EGFR T790M mutation along with activating mutations Ex19del and L858R. More real‐world data are needed to evaluate its efficacy and safety in treating locally advanced and metastatic non‐small cell lung cancer (NSCLC) following prior EGFR TKI treatment. Methods This multicenter retrospective study was conducted at seven university hospitals affiliated to the Catholic Medical Center (CMC) in Korea. A clinical data warehouse (CDW) platform was used to access and extract information. Results A total of 48 patients were assessed. The majority were female (75%) and diagnosed with adenocarcinoma (95.8%). All patients had the EGFR mutation at diagnosis, 27 (56.3%) had the exon 19 deletion, 20 (41.7%) had the L858R mutation, and one (2.0%) had the exon 18 mutation. The median progression‐free survival (PFS) was 15.4 months. At 6, 12, and 18 months, PFS rates were 79.1%, 53.6%, and 27.3%, respectively. When PFS was analyzed by prior TKI duration (<18 months vs. >18 months), significant differences were noted at the 6 and 9‐month mark (p = 0.013 and p = 0.010, respectively). In multivariate analysis for PFS, only prior TKI duration and ECOG score showed statistical significance (p = 0.026 and p = 0.049, respectively). In the multivariate analysis for OS, ECOG score showed statistical significance (p = 0.006). Among 48 patients, 34 (70.8%) experienced adverse events (AEs) related to lazertinib. The most frequent AEs were skin reaction (29.8%), diarrhea (21.3%), and peripheral neuropathy (20.8%). Conclusions The results suggest that lazertinib is effective in second or more line settings, with tolerable safety profile. More patient data are necessary to find possible prognostic markers associated with patient outcome.